"You seem to like your money, and we like our land" : a documentary history of the Salish, Pend d'Oreille, and Kootenai Indians, 1875-1889 - Bigart, Robert; McDonald, Joseph, 1933- (Salish Kootenai College Press, 2019)
"In the middle of the nineteenth century, the Salish, Pend d'Oreille, and Kootenai tribes of western Montana had navigated a world of military struggles with enemy tribes in alliance with the newly arrived tribe of white Americans. By the last quarter of the century - 1875-1889 - the paradigm had shifted, as the tribes worked to keep the peace with the white man while struggling to preserve tribal rights and assets from the onslaughts of the growing white population. In just fifteen years, the Flathead Reservation tribes careened from dramatic efforts to stay out of the 1877 Nez Perce War to seeking ways to get the white justice system to punish white men who murdered Indians. In 1889, the Missoula County Sheriff was actively pursuing Indians accused of murdering white men. Whites accused of killing Pend d'Oreille Chief Michelle's relatives and Kootenai Chief Eneas' son went unpunished. In 1882, tribal leaders negotiated terms for the sale of a railroad right of way through the reservation. Over the 1880s, Chief Charlo worked to secure the right of the Salish to remain in the Bitterroot and, if possible, to obtain enough government aid to help the establish a self-supporting Salish community in the Bitterroot Valley"--